Inter-Rater and Test–Retest Reliability of the German Pediatric Evaluation of Disability Inventory (PEDI-G). (1st August 2015) - Schulze, Christina; Kottorp, Anders; Meichtry, André; Lilja, Margareta; Page, Julie
ABSTRACT Activities of daily living (ADL) of children are widely assessed with the Pediatric Evaluation Disability Inventory (PEDI). This study examined test–retest and inter-rater reliability of the German PEDI (PEDI-G). During the adaptation of the PEDI nine items were added. In total, 117 parents of 53 children without and 64 children with a diagnosed physical disability from Austria, Germany, and Switzerland participated. Reliability was examined by intraclass correlation coefficient (ICC), standard error of measurement (SEM) and smallest detectable difference (SDD) for the Functional Skill Scale with and without added items and the Caregiver Assistance Scale. Cohen`s Kappa was used to calculate the reliability of the Modification Scale. All ICC's for test–retest and inter-rater reliability were above 0.75, indicating good to very good reliability. The SDD varied from 0.83–5.58 across PEDI domains and scales. For the Modification Scale, Cohen's weighted kappa varied from 0.25 to 1.00 indicating sufficient reliability for some but not all items. Our findings indicate that the Functional Skill Scale and the Caregiver Assistance Scale of the PEDI-G are reliable scales that can be used to evaluate ADLs of children with and without physical disability.